The performance of respiratory illness surveillance case definitions to detect Bordetella pertussis in children aged < 5 years seeking healthcare for respiratory illness in South Africa, 2017-2023 - Jensen, Katherine (Department of Public Health and Family Medicine, 2025)
Background: Pertussis is vaccine‐preventable and requires surveillance to guide interventions. Assessing the performance of syndromic surveillance and the World Health Organization (WHO) pertussis case definitions can improve sensitivity and accuracy in detecting laboratory‐confirmed Bordetella pertussis, ensuring effective monitoring in South Africa. Methods: We conducted a secondary analysis of respiratory illness surveillance data among children aged <5 years across sentinel sites from January 2017 through December 2023. Participants were enrolled as either outpatients eligible for influenza‐like illness (ILI), or hospitalised patients eligible for severe respiratory infection (SRI) surveillance. Nasopharyngeal swabs were tested for B. pertussis using polymerase chain reaction (PCR). Sensitivity, specificity, and other performance indicators of case definitions were evaluated against PCR results. Results: Of 23,887 participants, 23,640 (99.0%) had PCR results. B. pertussis was detected in 0.7% (30/4,125) from ILI and 1.6% (314/19,517) from SRI surveillance. Compared to the WHO pertussis case definition, a modified WHO pertussis case definition which includes apnoea and omits cough duration, improved sensitivity (ILI: 30.0% vs. 43.3%; SRI: 55.7% vs. 60.2%), but reduced specificity (ILI: 90.5% vs. 75.8%; SRI: 88.3% vs. 80.9% %). Negative predictive values were high for both definitions (ILI: 99.5% vs. 99.4%; SRI: 99.2% vs. 99.2%). The WHO pertussis case definition missed 44.3% of hospital laboratory‐confirmed cases, while the modified case definition missed 39.8%. Conclusion: Both WHO and modified pertussis case definitions missed many laboratory‐confirmed pertussis cases, likely underestimating disease burden. Revising the WHO pertussis case definition and integrating pertussis into syndromic surveillance is recommended to improve detection while optimising resources.